1965
DOI: 10.1038/bjc.1965.96
|View full text |Cite
|
Sign up to set email alerts
|

The histogenesis of mammary tumours induced in the rat by chemical carcinogens

Abstract: WHEREAS many studies deal with the histogenesis of mammary tumours in mice and in man (Bonser, Dossett and Jull, 1961), the literature contains relatively little information on the development of breast tumours in the rat (Noble and Cutts, 1959). Geschickter (1943) described the early neoplastic lesions induced by chronic oestrogenic stimulation but later studies employing chemical carcinogens for the induction of breast tumours were primarily concerned with the histology of advanced neoplasms (Ross, Scarf … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
0
1

Year Published

1969
1969
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 10 publications
3
10
0
1
Order By: Relevance
“…This was true in both unmated females, confirming the report of Middleton (1965), and in mated rats with unilateral lactation. Previous reports of decreasing tumour incidence with increasing age at DMBA administration (Huggins et al, 1961;Dao,1969) and of the protective effects of early but not delayed pregnancy (Dao et al, 1960) were, however, confirmed.…”
Section: Discussionsupporting
confidence: 88%
“…This was true in both unmated females, confirming the report of Middleton (1965), and in mated rats with unilateral lactation. Previous reports of decreasing tumour incidence with increasing age at DMBA administration (Huggins et al, 1961;Dao,1969) and of the protective effects of early but not delayed pregnancy (Dao et al, 1960) were, however, confirmed.…”
Section: Discussionsupporting
confidence: 88%
“…'i 100. (Faulkin et al, 1967;Middleton, 1965). Such turnours have not previously been reported in rats after inoculation of oncogenic viruses.…”
Section: Discussionmentioning
confidence: 90%
“…It has been reported that approximately 80% of the tumors arising are ovarian hormone-dependent (14,15). Rat mammary carcinomas are claimed to arise in small mammary ducts (16)(17)(18) or from hyperplastic alveolar nodules (19,20). The work presented here was undertaken to describe the histopathogenesis of rat DMBA-induced ovary-dependent tumors and ovary-independent mammary tumors in order to identify their site(s) of origin and to reexamine the preneoplastic nature of DMBAinduced mammary gland dysplasias.…”
mentioning
confidence: 99%